Conservation and availability of plant genetic diversity: innovative strategies and technologies - Dulloo, Mohammad Ehsan (International Society for Horticultural Science, 2015)
The conservation of plant genetic diversity underpins the future of agriculture and food security and is critical to ensure the ability of future generations to cope with global environmental changes. Yet plant genetic resources, including those of horticultural crops and their wild relatives, are increasingly being lost, with irreversible global implications. Despite recognition of the value of plant genetic diversity by breeders and farmers, its exact status and trends are largely unknown, and investments in its conservation and monitoring are dwindling. This calls for the development of innovative cost-effective conservation strategies and technologies ex situ, on farm and in the wild. A brief overview will be presented of the technological advances and approaches for: ex situ conservation (seedbanks, in vitro, cryopreservation DNA banks, field collections and botanic gardens), on-farm management (involving community-based management), and in situ conservation (in wild habitats). Strategies for prioritizing, measuring and monitoring the trends in genetic diversity, including a Red List system for threatened cultivated plants will also be presented and discussed. To cope with future challenges, especially climate change, global collaboration between the agriculture and environment sectors will be required. We will need more effective conservation and freer exchange of information and germplasm. This will require an effective information mechanism that will connect data about the status and trends of plant diversity to decision makers for conservation and development outcomes.